Adaptation of irrigated soy cultivars in sandy soils (Research, Society and Development, 2021)
With irrigation, producers can explore areas that were previously not arable, and maximize their productivity. With the hypothesis of adaptation of soybean cultivars in sub-optimal conditions of water in the soil, the objective was to evaluate the different varieties of soybean (Glycine max (L.)) in sandy soils under dry and irrigated conditions. The design used was the Randomized blocks in a strip scheme consisting of the cultivars DM 80I79 IPRO, BONUS IPRO, Maracaí IPRO, DM 75I76, Foco IPRO and Aporé IPRO under two conditions of water in the soil (dry and irrigated) with 4 repetitions per treatment , totaling 48 evaluated plots. Plant height, pod insertion height, number of plants, number of pods per plant, number of grains per plant and number of branches and number of nodes, mass of one hundred grains and grain yield were analyzed. In sandy soils, the DM 80I79 IPRO variety, when subjected to irrigation, shows an increase in productivity. When the cultivars were subjected to irrigation, all expressed an increase in productivity, a fact proven by the non-statistical differentiation between cultivars, managing to balance their productive potential, varying only due to characteristics of resistance to water deficit, causing productive variability between them.